Tattoo histories transcultural perspectives on the narratives, practices, and representations of tattooing - Kloss, Sinah Theres (Routledge studies in cultural history, 2020)
"Tattoo Histories is an edited volume which analyzes and discusses the relevance of tattooing in the socio-cultural construction of bodies, boundaries, and identities, among both individuals and groups. Its interdisciplinary approach facilitates historical as well as contemporary perspectives. Rather than presenting a universal, essentialized history of tattooing, the volume's objective is to focus on the entangled and transcultural histories, narratives, and practices related to tattoos. Contributions stem from various fields, including Archaeology, Art History, Classics, History, Linguistics, Media and Literary Studies, Social and Cultural Anthropology, and Sociology. They advance the current endeavour on the part of tattoo scholars to challenge Eurocentric and North American biases prevalent in much of tattoo research, by including various analyses based in locations such as Malaysia, Israel, East Africa, and India. The thematic focus is on the transformative capacity of tattoos and tattooing, with regard to the social construction of bodies and subjectivity; the (re-)creation of social relationships through the definition of (non-)tattooed others; the formation and consolidation of group identities, traditions, and authenticity; and the conceptualization of art and its relevance to tattoo artist-tattooee relations"--